Comparison of growth in different glucose concentrations and biofilm formation among Candida glabrata strains isolated from various anatomical sites - Muhammad Zaim Mohd Shairy.
The incidence of Candida glabrata infections has increased significantly over the past decades. C. glabrara causes a wide range of infections, ranging from oral thrush to deep-seated organ infection. These infections are associated with important virulence factors of C. glabrata; among which are its adherence capacity to host surfaces or abiotic medical devices to form biofilm and resistance toward antifungal drugs. Different anatomical sites are found to have different level of nutrients and conditions which make some isolates more prone to adhere and form biofilm depending on their isolation sites. This study aimed to characterize and compare C. glabrata strains isolated from various anatomical sites on their growth rate in different glucose concentrations and biofilm formation ability. A total of 17 C. glabrata strains isolated from different anatomical sites (blood, vagina, tissue and penis) were used and routinely cultivated on Sabouraud Dextrose (SD) medium. Cells were suspended in Yeast Nitrogen Base (YNB) broth with defined glucose concentration (0.01%, 0.1% and 2%) for growth profiling assay. Cells were suspended in RPMI-1640 medium (2% glucose concentration) and placed in 96-wells plate for biofilm growth. Biofilm formation was evaluated by measuring its metabolic activity using semi quantitative 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilde (XTT) reduction assay. Each experiment was performed in triplicate for at least three independent experiments. Statistical analysis was performed using ANOVA and unpaired T-test with P<0.05 is considered as statistically significant. There was no significant interaction between different glucose concentrations and isolation sites on the growth of C. glabrara strains. Glucose was found to be extremely significant in regulating the growth of C.glabrata strains as their growth rates were higher with the increment of glucose concentration. Nevertheless, their growth was not significantly influenced according to their respective isolation sites. C. glabrata strains isolated from blood had higher ability to form biofilm compared to strains isolated from tissues. vagina and penis. In conclusion, changes in general behaviour and pathogenicity of C. glabrata is contributed by strain adaptation to the isolated site where they originated. It is important to consider the potential influence of different isolation sites on C. glabrata growth rate and biofilm formation when designing any experimentation and interpreting data. Kqwords: Candida glabrata, growth, glucose concentrations, biofilm. anatomical sites